Can southern ocean eddy effects be parameterized in climate models? - Bryan, Frank (author); Gent, Peter (author); Tomas, Robert (author) (Journal of Climate, 2014)
Present-day control and 1% yr⁻¹ increasing carbon dioxide runs have been made using two versions of the Community Climate System Model, version 3.5. One uses the standard versions of the ocean and sea ice components where the horizontal resolution is 1° and the effects of mesoscale eddies are parameterized, and the second uses a resolution of 1/10° where the eddies are resolved. This is the first time the parameterization has been tested in a climate change run compared to an eddy-resolving run. The comparison is made not straightforward by the fact that the two control run climates are not the same, especially in their sea ice distributions. The focus is on the Antarctic Circumpolar Current region, where the effects of eddies are of leading order. The conclusions are that many of the differences in the two carbon dioxide transient forcing runs can be explained by the different control run sea ice distributions around Antarctica, but there are some quantitative differences in the meridional overturning circulation, poleward heat transport, and zonally averaged heat uptake when the eddies are parameterized rather than resolved.